Visitors' satisfaction toward activities and services at Perhentian Island Marine Park, Terengganu / Wan Ahmad Wan Hasan - Wan Hasan, Wan Ahmad (2014)
Among the important factors need to be considered in order to make the tourism place become a focai point is by fulfilling the visitors' satisfaction. When the visitors satisfied with the activities and services provided at that place, for sure they will revisit and may recommend it to others.This thing is indirectly makes the place to became an attraction towards visitors. For Perhentian Island Marine Park, Terengganu which a place that have chosen to conduct the study, there are still no research have been conducted to identify the visitors' satisfaction. Thus, this research has been conducted and identified the level of visitors' satisfaction toward activities and services at Perhentian Island Marine Park, Terengganu. Besides that, the visitation factors also have been identified from this research. In order to obtain the result for this study, questionnaires have been distributed to the visitors who came to this island without emphasizing whether they are local or foreign visitors. Next, all of these questionnaires have been analyzed and the findings revealed that there still a lot of improvement needs to be done by the management of marine park and tourism operators especially for land activities. While for the facilities that have been provided were satisfied by the visitors, except for the personnel at the island which also needs to be look back by the management of marine park and tourism operators in providing a better services